Statystyczna analiza struktury obszarowej gospodarstw rolnych w Polsce - Kukuła, Karol (Statistical Analysis of Areal Structure of Farms in Poland, 2005)
The paper presents the analysis of areal structure of farms at the level of voivodships in Poland.Farms have been divided into four groups with respect to their areas:I - up to 5 ha,II - within the interval of 5 to 10 ha,III - within the interval of 10 to 30 ha,IV - above 30 ha.As a result of the application of the relevant taxonomic procedure four groups of voivodships of similar areal structure of farms have been obtained. Each group has been shortly characterised.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 525-531